A review of additive manufacturing of Mg-based alloys and composite implants - Zamani, Yasamin; Ghazanfari, Hadi; Erabi, Gisou; Moghanian, Amirhossein; Fakić , Belma; Hosseini, Seyed Mohammad; Pasha Mahammod, Babar (Journal of Composites and Compounds, 2021)
Magnesium based materials are considered promising biodegradable metals for orthopedic bone implant applications as they exhibit similar density and elastic modulus to that of bone, biodegradability, and excellent osteogenic properties. The use of Mg based biomaterials eliminates the limitations of currently used implant materials such as stress shielding and the need for the second surgery. Recently, the development of Mg-based implants has attracted significant attention. Additive manufacturing is one of the effective techniques to develop Mg based implants. Additive manufacturing which could be named 3D printing is a transformative and rapid method of producing industrial parts with in the acceptable dimensional range. Therefore, recent investigations have tried to apply this method for the development of Mg-based implants. This state-of-the-art review focuses on the additive manufacturing of Mg biodegradable materials and their in-vitro corrosion and degradation, and mechanical properties. The future directions to develop Mg biodegradable materials are reported through summarization of current achievements.